Fermented Pueraria Lobata extract ameliorates dextran sulfate sodium-induced colitis by reducing pro-inflammatory cytokines and recovering intestinal barrier function - Choi, Seungho; Woo, Jong-Kyu; Jang, Yeong-Su; Kang, Ju-Hee; Jang, Jung-Eun; Yi, Tae-Hoo; Park, Sang-Yong; Kim, Sun-Yeou; Yoon, Yeo-Sung; Oh, Seung Hyun (Laboratory animal research, 2016)
Inflammatory bowel disease is a chronic inflammatory disorder occurring in the gastrointestinal track. However, the efficacy of current therapeutic strategies has been limited and accompanied by side effects. In order to eliminate the limitations, herbal medicines have recently been developed for treatment of IBD. Peuraria Lobata ( Peuraria L. ) is one of the traditional herbal medicines that have anti-inflammatory effects. Bioavailability of Peuraria L. , which is rich in isoflavones, is lower than that of their fermented forms. In this study, we generated fermented Peuraria L. extracts (fPue) and investigated the role of fPue in inflammation and intestinal barrier function in vitro and in vivo . As the mice or intestinal epithelial cells were treated with DSS/fPue, mRNA expression of pro-inflammatory cytokines was reduced and the architecture and expression of tight junction proteins were recovered, compared to the DSS-treated group. In summary, fPue treatment resulted in amelioration of DSS-induced inflammation in the colon, and the disrupted intestinal barrier was recovered as the expression and architecture of tight junction proteins were retrieved. These results suggest that use of fPue could be a new therapeutic strategy for treatment of IBD.